Evaluation of a method to measure the ratio of pelvic limb to thoracic limb girth in dogs - Elisabeth A. Fox; Kirsty E. Oliver; Matthew W. Brunke (Veterinary Evidence, 2023)
Objective: To determine if a landmark-incorporated limb girth measurement in sound dogs, utilising the greater trochanter and the acromion process, would be both reliable and have a consistent ratio between pelvic limb (PL) and thoracic limb (TL) muscle measurements.